Antenatal management of multiple pregnancies within the UK: A survey of practice. (November 2020) - Gent, Joanna; Nanda, Surabhi; Khalil, Asma; Sharp, Andrew
Abstract: Objectives: To identify variation in the antenatal management of multiple pregnancy. The UK has 10, 000 twin pregnancies per year. There is established guidance on the management of dichorionic (DC) and monochorionic (MC) twin pregnancy from both the RCOG and NICE, however it is likely that the provision and practice of multiple pregnancy management varies amongst units. Design: Questionnaires were posted to 151 UK maternity units in 3 rounds from May to November 2019. Results: 60 responses were received (range 11, 500 to 501 deliveries), with annual multiple pregnancy rates of 190 to 4. 25 % of units did not offer a dedicated twin clinic and less than 15 % of units provided dedicated multiple pregnancy midwifery staff for intrapartum and postnatal care. Cervical length screening was performed in 24 % of units with 84 % of units offering treatment for a short cervix. 15 % of units prescribed Aspirin to all multiples, 47 % prescribing 75 mg and 43 % 150 mg. Monitoring of MC pregnancies varied with 18 % of units not measuring Middle Cerebral Artery and 29 % Ductus Venosus Dopplers. Mean caesarean section rate was 61.7 %. Delivery was offered from 37 weeks in 93 % of DC twins and from 36 weeks in 90 % MC twins. 5% of MC twins were given non labouring prophylactic antenatal steroids. Conclusion: Despite well-established national guidance for twin pregnancy management there remains a wide variation in practice among units in the provision and antenatal management of multiple pregnancies throughout the UK. The exact reasons for this variation require further exploration.